Comparative evaluation of hydraulic fracturing performance in vertical and horizontal wells using pipesim software - Al-Hilali, Huda J.TH.; Almahdawi, Faleh H. M.; Hasiholan, Bonavian; Mukhtar, Yasir M. F. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
This research paper uses pipesim software to reproduce and evaluate well performance, comparing vertical and horizontal wells using hydraulic fracturing. It examines the impact of key parameters, such as fracture length, width, permeability, and fracture number, on production improvement. In low-permeability reservoirs, simulation studies indicate that horizontal wells often achieve higher production rates than vertical wells, largely due to improved reservoir and fracture connectivity. Productivity in the vertical well increased to 300(stb/d), while in the horizontal well, it increased to over 9,000 (stb/d) after using hydraulic fracturing. The results indicate that fracture width has less of an impact on the performance of vertical wells than horizontal wells, although fracture length and fracture number significantly influence horizontal well productivity. This disparity underscores the need for strategic fracture design and well selection to optimize oil production under changing reservoir conditions. The research paper emphasizes the need to use advanced modeling tools such as PIPESIM to accurately predict well performance and guide decision-making in hydraulic fracturing operations. Tailor-made fracturing techniques based on reservoir properties can significantly enhance continuous production efficiency and extend well life.